Gut Microbiota Types between Well-Grown and Stunted Children: A Systematic Review - Eriyanti Astika; Ahsanal Kasasiah; Jekmal Malau; Al Mukhlas Fikri (Universitas Labuhanbatu, 2024)
Stunting, one of the malnutrition in the prenatal period up to the first two years of life and often exacerbated by recurrent gastrointestinal infections after birth. This study explores from various databases including Pubmed, Scopus, Science Direct, Sage Journal, Springer Link, with keywords: